การดูดซับของไหลตัดชิ้นงานบนเม็ดไคโทซานเชื่อมขวางที่มีรูพรุน - พัชรินทร์ ทองดอนเอ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this work is to study adsorption capacity of cutting fluid onto chitosan beads, porous chitosan beads, crosslinked chitosan beads and porous crosslinked chitosan beads. The effect of pH, adsorbent dosage, initial concentration of cutting fluid, temperature and contact time on adsorption capacity were investigated. From the experimental results, it was found that the adsorption capacity increased with initial cutting fluid concentration. Higher adsorption capacity was obtained when the operating condition was in an acidic. At acidic condition, more amount of amine groups in chitosan is protonated and lead to electrostatic interaction between negative charge of cutting fluids and the positive surface charge of adsorbents. The evaluated maximum monolayer adsorption capacities for chitosan beads, porous chitosan beads, crosslinked chitosan beads and porous crosslinked chitosan beads were 223.5, 1906.4, 1254.1 and 2997.9 mg/g, respectively. The equilibrium adsorption data were well described by the Langmuir isotherm model. The kinetic data fits to pseudo-second-order kinetic model and enthalpy (ΔH°), Gibbs free energy (ΔG°) from thermodynamic data elucidated that the adsorption is a spontaneous and endothermic process. The adsorbents were characterized by BET, SEM, FT-IR and Zeta potential.